Inhibiting the pathological changes of PASMCs is an effective approach for medicinal plants or secondary metabolites in treating pulmonary hypertension - Liang, Qi; Gou, Hanghang; Zhu, Yi; He, Lin; Chen, Liping; Zhang, Chuantao; Ai, Li (Frontiers in Pharmacology, 2026)
Pulmonary hypertension (PH) is a progressive cardiovascular disease characterized by increased pulmonary vascular resistance and structural remodeling of pulmonary vessels, leading to poor clinical outcomes and high mortality. pulmonary artery smooth muscle cells (PASMCs) migration, apoptosis and abnormal proliferation are the main pathological features leading to the occurrence of PH. Increasing evidence suggests that inhibition of PASMCs pathological changes contributes to the improvement of PH. However, the current clinical treatment of PH is limited, and medicinal plants or secondary metabolites are gradually recognized as potential treatment options for PH. Therefore, this article focuses on inhibiting the abnormal pathological changes of PASMCs, and analyzes and summarizes the mechanism and process of medicinal plants or secondary metabolites in the treatment of PH by inhibiting the abnormal proliferation of PASMCs, so as to provide a direction for the development of medicinal plants or secondary metabolites for the treatment of PH.